Results from a phase 1 multiple ascending dose study demonstrating safety and selectivity of aldosterone synthase inhibitor CIN-107. (3rd October 2022) - Freeman, M; Bond, M; Murphy, B; Isaacsohn, J
Abstract: Background: CIN-107 is a highly potent, selective, and competitive small molecule inhibitor of aldosterone synthase that is a potential treatment for disorders associated with elevated aldosterone levels, including hypertension and primary aldosteronism. This randomized, double-blind, placebo-controlled phase 1 study evaluated the safety, pharmacokinetics, and pharmacodynamics of multiple ascending doses of CIN-107 in healthy volunteers. Methods: Subjects were randomized into 5 cohorts to receive CIN-107 or placebo once daily for 10 days. Cohorts 1 and 2 were placed on a low salt diet to stimulate aldosterone production and were administered 2.5 or 5.0 mg oral CIN-107, respectively. Cohorts 1 and 2 also underwent an adrenocorticotropic hormone (ACTH) challenge to increase aldosterone and cortisol levels to evaluate the specificity of CIN-107 for targeting aldosterone synthase. Cohorts 3, 4, and 5 were placed on a normal salt diet and were administered 1.5, 2.5, or 0.5 mg oral CIN-107, respectively. Blood samples were collected prior to and after dosing on days 1 and 10 for measurement of plasma CIN-107 concentrations to characterize single-dose and steady-state pharmacokinetics. Pharmacodynamic measurements included plasma aldosterone, cortisol, and electrolytes. Safety assessments included physical examination, electrocardiograms, orthostatic vital signs, and clinical laboratory evaluations. Results: 54 subjects completed the study. There were no deaths, serious adverse events, or discontinuations due to treatment-emergent adverse events (TEAEs). All TEAEs in subjects receiving CIN-107 were mild in severity (Table 1). Plasma concentrations of CIN-107 increased proportionally with ascending doses. CIN-107 was rapidly absorbed, with peak concentrations observed within 4 hours after dosing. The concentration of plasma CIN-107 declined in an apparent biphasic manner with a half-life of 26 to 31 hours. A dose-dependent reduction of plasma aldosterone was observed with CIN-107 doses ≥1.5 mg, regardless of normal or low salt diet. Decreases in plasma aldosterone were observed starting on Day 1 and were sustained, with levels reduced by approximately 51–73% on Day 10 (Figure 1). The inhibition of aldosterone synthase by CIN-107 had no impact on plasma cortisol. CIN-107 resulted in mild dose-dependent decreases in plasma sodium levels and increases in potassium levels, as would be expected from the observed reduction in aldosterone. Conclusions: Oral administration of CIN-107 was safe and well tolerated in all subjects and resulted in dose-dependent increases in plasma CIN-107 with a half-life that supports once-daily dosing. The dose-dependent decrease in plasma aldosterone and lack of effect on cortisol demonstrate the selective blockade of aldosterone synthase and support continued study in ongoing phase 2 clinical trials evaluating the efficacy and safety of CIN-107 for treatment-resistant or uncontrolled hypertension and primary aldosteronism. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): CinCor Pharma Inc